Perjuangan Perempuan Dalam Film Kaluna Home Sweet Loan Sutradara Sabrina Rochelle Kalangle - Pratiwi, Rika Putri; Atmaja, Loliek Kani; Yuniati, Ira; Lisdayanti, Septina (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to describe the women’s struggle for gender justice depicted in the film Kaluna Home Sweet Loan. The research method used is descriptive qualitative with content analysis techniques. The research data consists of dialogue excerpts from the film that demonstrate women's independence, rejection of unfair domestic roles, resistance to gender inequality, criticism of stereotypes of women's roles, and support for equal rights and opportunities. Data collection was conducted through documentary study by watching the film, transcribing the dialogue, and classifying the data according to the research focus. The results show 66 items of data divided into five sub-aspects: women's independence in decision-making (18 items), rejection of unfair domestic roles (9 items), rejection of gender inequality (14 items), criticism of stereotypes of women's roles (13 items), and support for equal rights and opportunities (12 items). These findings demonstrate that the film Kaluna Home Sweet Loan not only provides entertainment but also represents the reality of women's struggle to demand equal rights and fight gender discrimination in society.